ROUTLEDGE COMPANION TO CHINESE PHILOSOPHY ([S.l.])
1 online resource
Keywords: The Routledge Companion to Chinese Philosophy features more than 40 chapter-length introductions to the concepts, claims, and arguments that animate the Chinese philosophical tradition. Taking a topic-by-topic rather than text-by-text approach, this Companion aims at helping contemporary Anglophone readers access the philosophical riches of the Chinese tradition by balancing close analysis with broad contextualization.The book is divided into four "Acts" that reflect system-level changes in how the Chinese philosophical conversation has been conducted: Act I draws primarily on pre-imperial texts, foregrounding competition among persuaders in the absence of a geographical or canonical center of gravity. Act II focuses on the early imperial centralization of intellectual culture around the corpus of Confucian classics. Act III restructures the conversation space according to the radically innovative priorities of Buddhism. Act IV focuses on Neo-Confucianism, which combines some of the priorities of Act II with the ongoing legacy of Act III. Within each Act, contributors focus on topics like religious and political thought, ethics and self-cultivation, philosophical anthropology and theory of agency, language, epistemology, metaphysics, hermeneutics, and debate. This volume is essential reading for students, academics, and philosophers with an interest in Chinese philosophy.